Desafios da implementação da inteligência artificial no sistema judicial: como a Academia e o Judiciário podem trabalhar em conjunto para racionalizar as transformações decorrentes da adoção da Inteligência Artificial no Sistema Judicial - Campos, Eduardo Villa Coimbra (Universidade do Vale do Rio dos Sinos, 2023)
Artificial Intelligence is consolidated and disseminated in innumerous fields of human knowledge and will have repercussions and consequences that will reach the Judicial System and must be faced. The use of machine learning algorithms, however, raises questions and fears. In this context, the problem delimited in the present is related to the need to analyze the potential inevitability of the confrontation between the consequences of the implementation of AI and the Law in general and the Judicial System in particular. Accordingly, its general objective will be to report and analyze the transformations and challenges that Artificial Intelligence will bring to the Judicial System, and, also, its specific objective to formulate a collaborative proposal between the System itself and the Academy to face such consequences. The consequent challenges can be classified as exogenous, produced outside the System, but which have an impact on it, and endogenous, resulting from the use of the technology in question within the Judicial System itself. The methodology used for this purpose was based on research and bibliographic review, in foreign and national sources, data collection and case studies on the use of AI in general and in the Judicial System, as well as on the use of national academic production by the Judicial power. As a result of the research carried out, it was found that the implementation of such technological innovation has a disruptive nature and, consequently, will bring profound transformations, which is why it needs to be done in a transparent and ethical way, with a minimum and possible degree of explainability. It was also discovered that, nevertheless, it is already consolidated at a global and national level, without its opacity having been sufficiently addressed. Therefore, critical reflection, debate and formulation of propositions are imperative. The proposal formulated, at the end, of a collaborative intersection between the Judiciary and the Academy is an alternative that can facilitate this approach, enhancing the positive effects and minimizing the negative ones.
Keywords: Inteligência artificial; Desafios; Ética; Dignidade humana; Estado democrático de direito; Sistema judicial; Academia; Interseção; Artificial intelligence; Challenges; Ethics; Human dignity; Rule of Law; Judicial system; Academy; Intersection; ACCNPQ::Ciências Sociais Aplicadas::Direito